Monitor climate-smart agricultural interventions with a real-time participatory tool - Eitzinger, Anton; Mwongera, Caroline; Läderach, Peter R.D.; Acosta, Mariola; Ampaire, Edidah L.; Lamanna, Christine; Mwungu, Chris Miyinzi; Shikuku, Kelvin Mashisia; Twyman, Jennifer; Winowiecki, Leigh Ann (International Center for Tropical Agriculture, 2017)
Climate-smart agricultural (CSA) interventions often require “fine-tuning” i.e. feedback from multiple stakeholders e.g. farmers, extension agents, NGO workers, and policy implementers on their relevance in a given context.